IMPLEMENTATION OF THE PRINCIPLES OF INTERNAL BALANCE BUYING AND BUYING LAND - Widodo, Sigit; Endang Retnowati; Agam Sulaksono (Cahaya Ilmu Bangsa, 2024)
ABSTRAC Land is an asset that is really needed by society, where human needs for land will continue to increase, and accessibility to land is increasingly limited. The need for land is monetary, social and mechanical. Land registration is a prerequisite in efforts to organize and regulate the allocation, control, ownership and use of land, including to resolve various land problems. Land registration is intended to provide certainty of rights and legal protection for holders of land rights by proving a land certificate, as a controlling instrument in the use and benefits of land. The transfer of land rights due to sale and purchase should be carried out before the PPAT by making a binding sale and purchase agreement in accordance with Government Regulations. Number 24 of 1997 concerning Land Registration in the practice of buying and selling land, buying and selling is based on the power contained in the land sale and purchase agreement, so the researcher wrote about